1. выражение: -2 ab⁵ ·(-3 a⁴b²)³ 2. решите уравнение: а) 6(x-3)=8x -(3x-4) б)4x-6,4=0 3. выполните действия: 15y²+7y-(13y-5y²) (а+2)·(а²-а-3) (4аb²-6a²b): 2ab 4. : 7y·(y+x-p)-7p·(x-y-p)+7x·(x-y+p) заранее .

Щощо Щощо    3   29.05.2019 06:10    0

Ответы
oksanasyxovaro oksanasyxovaro  27.06.2020 12:46
1)) 54 * a^13 * b^11
2a)) 6x-18 = 8x-3x+4
x = 22
2b)) x = 6.4 / 4 = 1.6
3)) 15y^2 + 7y - 13y + 5y^2 = 20y^2 - 6y
... = a^3 - a^2 - 3a + 2a^2 - 2a - 6 = a^3 + a^2 - 5a - 6 
(4ab^2) / (2ab) - (6a^2b) / (2ab) = 2b - 3a 
4)) 7y^2 + 7xy - 7yp - 7xp + 7yp + 7p^2 + 7x^2 - 7xy + 7xp = 7*(x^2 + y^2 + p^2)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра